Particle swarm optimization for solving combine economic and emission dispatch / Nazirah Muhammad - Muhammad, Nazirah (2014)
The main objective of power system optimizing with enviromental consideration is to schedule the generating units within the best operating limits in order to minimize the total operating cost of power generation while considering the enviromental constraint into account.